Digitalisasi Layanan Laundry: Implementasi Sistem Pemesanan dan Kasir Berbasis Web pada UMKM LBC Laundry Malang - Abitara, Alvin Bintang; Triyanna Widiyaningtyas; Sari, Heni Vidia; Ahmad Reza; Adrian Juhari (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to design and implement a web-based ordering and cashier system for LBC Laundry, an MSME in Malang, to improve operational efficiency, financial reporting accuracy, and information transparency for customers. The program was carried out through field observation, needs assessment using semi-structured interviews and Focus Group Discussions (FGDs) with the business owner, system design based on a user-centered design (UCD) approach, iterative system development using the MERN Stack framework with CRUD (Create, Read, Update, Delete) functionality, followed by training, mentoring, and evaluation. Quantitative data were analyzed using descriptive statistics by comparing key performance indicators before and after the program implementation. The results demonstrated an 80% improvement in transaction efficiency, with the average transaction time decreasing from 5 minutes to 1 minute per customer. In addition, data entry errors were reduced to zero throughout the one-month evaluation period, while the accuracy of financial reporting reached 100% through real-time reporting capabilities. The MSME owner provided positive feedback, indicating that the system simplified business operations and enhanced information transparency for customers. Furthermore, the system has the potential to be further developed into a mobile application to improve accessibility and support the long-term digital transformation of MSMEs.